Relationships between the responses of triglyceride-rich lipoproteins in blood plasma containing apolipoproteins B-48 and B-100 to a fat-containing meal in normolipidemic humans. - Schneeman, B O (1993)
The concentration of triglyceride-rich lipoproteins containing apolipoprotein (apo) B-48 (chylomicrons) and apo B-100 (very low density lipoproteins) was measured in blood plasma of healthy young men after an ordinary meal containing one-third of daily energy and fat. Plasma obtained in the postabsorptive state and at intervals up to 12 hr after the meal was subjected to immunoaffinity chromatography against a monoclonal antibody to apo B-100 that does not bind apo B-48 and a minor fraction of apo B-100 rich in apo E. Measurements of the concentrations of components of the total and unbound triglyceride-rich lipoproteins separated from plasma by ultracentrifugation showed that about 80% of the increase in lipoprotein particle number was in very low density lipoproteins containing apo B-100 and only 20% was in chylomicrons containing apo B-48 that carry dietary fat from the intestine. The maximal increments and the average concentrations of apo B-48 and B-100 during the 12 hr were highly correlated (r2 = 0.80), suggesting that preferential clearance of chylomicron triglycerides by lipoprotein lipase leads to accumulation of hepatogenous very low density lipoproteins during the alimentary period. The composition of the bulk of very low density lipoproteins that were bound to the monoclonal antibody changed little and these particles contained about 90% of the cholesterol and most of the apo E that accumulated in triglyceride-rich lipoproteins. The predominant accumulation of very low density lipoprotein rather than chylomicron particles after ingestion of ordinary meals is relevant to the potential atherogenicity of postprandial lipoproteins.